Statistical Inference as a Bargaining Game - Ley, Eduardo (IMF Working Papers; Working Paper, 2002)
This paper extends the analogy, previously established by Learner (1978a), between a Bayesian inference problem and an economics allocation problem to show that posterior modes can be interpreted as optimal outcomes of a bargaining game. This bargaining game, over a parameter value, is played between two players: the researcher (with preferences represented by the prior) and the data (with preferences represented by the likelihood).